PERAN MEDIASI ORIENTASI KEWIRAUSAHAAN DAN ORIENTASI PASAR PADA PENGARUH CULTURAL INTELLIGENCE TERHADAP KINERJA UKM - Agus Satria Pramudana, Komang; Santika, I Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.01.TAHUN.2023DO - 10.24843/EEB.2023.v12.i01.p16, 2023)
This study examines the mediating role of entrepreneurial orientation and market orientation on the influence of cultural intelligence on the performance of small and medium export enterprises in Bali. The research was conducted on 50 small and medium export businesses in Bali. The data collection method uses a survey method with research instruments in the form of online questionnaires. Data measurement uses a semantic differential scale measurement unit which is an interval measurement scale. The collected data were analyzed using statistical tools, namely descriptive statistics and inferential statistics (SEM-PLS) to draw conclusions. The results of the study show that cultural intelligence has a positive effect on entrepreneurial orientation, market orientation, and the performance of small and medium export businesses in Bali. Entrepreneurial orientation has a positive effect on market orientation and the performance of export small and medium enterprises in Bali. Market orientation has a positive effect on the performance of small and medium export businesses in Bali. Entrepreneurial orientation and market orientation significantly mediate the influence of cultural intelligence on the performance of small and medium export enterprises in Bali.